2019
DOI: 10.1002/app.47587
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wear properties of a polyether ether ketone polymer by incorporation of carbon and glass fibers

Abstract: Some properties of polymers can be improved through the incorporation of carbon and glass fibers into the polymer matrix. In this research, the wear resistance of two polymer composites CF‐polyether ether ketone (PEEK) and GF‐PEEK were compared with the virgin PEEK. The wear resistance was assessed by Pin on Disk tests performed using a range of reinforced polymer pins tested against a steel disk. The influence of load, sliding velocity, counter‐surface hardness, and reinforcement concentration and type, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have confirmed that both the lubrication conditions and working conditions highly affect the wear behavior of polymers 16,17 . Similar studies have also been done on PEEK and confirm that PEEK's wear behavior is also highly influenced by the former two factors 18–22 . Laux et al 18 have studied the wear behavior and the transfer film phenomena of PEEK under different working conditions.…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies have confirmed that both the lubrication conditions and working conditions highly affect the wear behavior of polymers 16,17 . Similar studies have also been done on PEEK and confirm that PEEK's wear behavior is also highly influenced by the former two factors 18–22 . Laux et al 18 have studied the wear behavior and the transfer film phenomena of PEEK under different working conditions.…”
Section: Introductionmentioning
confidence: 63%
“…(P < 0.01) increasing resistance to the use of metal implants. As a result, PEEK has attracted attention for use in implants because of its excellent physical and chemical properties [22,23]. Because the high incidence of implant failure is an important cause of peri-implant inflammation, we designed a PEEK implant surface with antibacterial In this study, due to 3D mesh sponge structure, GO nanosheets can be adsorbed to the surface, and the SEM results showed that GO uniformly covered the surface.…”
Section: Discussionmentioning
confidence: 99%
“…While pure titanium and titanium alloy implant materials have long been used as materials for orthopaedic and dental implants [ 21 ], in recent years, patients have shown increasing resistance to the use of metal implants. As a result, PEEK has attracted attention for use in implants because of its excellent physical and chemical properties [ 22 , 23 ]. Because the high incidence of implant failure is an important cause of peri-implant inflammation, we designed a PEEK implant surface with antibacterial properties that is expected to advance the development of antimicrobial implants.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that the tensile strength and modulus of PET/CF composites increased with an increasing aspect ratio of CF (under the same loading of CF); this increase accompanied the decreased impact strength and elongation at break 20 wt% of the CF. Hamilton et al [105] reported that 20 wt% of CF could increase thermoplastic composites' wear resistance based on the PEEK matrix. Similar observations have been noted by Karsli and Aytac [106], who reported an enhancement of wear properties by incorporating CF into PEEK composites.…”
Section: Mechanical Strength and Modulus Of Cfrtpmentioning
confidence: 99%